Assessing the impacts of natural resource management interventions in agriculture: Concepts, issues and challenges - Freeman, H.A.; Shiferaw, B.; Swinton, S.M. (CAB International, 2005)
This chapter identifies key issues involved in assessing the impacts of natural resource management (NRM) interventions. Such interventions include adoption of changed NRM practices arising from investments in research and outreach that are implemented through NRM projects, programmes, and policies. The focus is on impact analysis of NRM interventions, not on conducting NRM projects per se. The sections of this paper discusses the purpose of impact assessment, followed by the underlying concepts and techniques for conducting impact assessment, followed by the underlying concepts and techniques for conducting impact assessment. This is followed by a discussion of the special challenges that complicate impact assessment of NRM interventions. The chapter ends by providing an overview of the conceptual and empirical approaches for NRM impact assessment.